Oculopharyngeal Muscular Dystrophy as a Paradigm for Muscle Aging - Raz, Yotam; Raz, Vered (Frontiers in Aging Neuroscience, 2014)
Symptoms in late-onset neuromuscular disorders initiate only from midlife onwards and progress with age. These disorders are primarily determined by identified hereditable mutations, but their late-onset symptom manifestation is not fully understood. Here, we review recent research developments on the late-onset autosomal dominant oculopharyngeal muscular dystrophy (OPMD). OPMD is caused by an expansion mutation in the gene encoding for poly-adenylate RNA binding protein1 (PABPN1). The molecular pathogenesis for the disease is still poorly understood. Despite a ubiquitous expression of PABPN1, symptoms in OPMD are limited to skeletal muscles. We discuss recent studies showing that PABPN1 levels in skeletal muscles are lower compared with other tissues, and specifically in skeletal muscles, PABPN1 expression declines from midlife onwards. In OPMD, aggregation of expanded PABPN1 causes an additional decline in the level of the functional protein, which is associated with severe muscle weakness in OPMD. Reduced PABNPN1 expression in muscle cell culture causes myogenic defects, suggesting that PABPN1 loss-of-function causes muscle weakness in OPMD and in the elderly. Molecular signatures of OPMD muscles are similar to these of normal muscle aging, although expression trends progress faster in OPMD. We discuss a working hypothesis that aging-associated factors trigger late-onset symptoms in OPMD, and contribute to accelerated muscle weakness in OPMD. We focus on the pharyngeal and eyelid muscles, which are often affected in OPMD patients. We suggest that muscle weakness in OPMD is a paradigm for muscle aging.